ANALISA HUBUNGAN LEADERSHIP STYLE TERHADAP LEARNING ORGANIZATION DALAM MENINGKATKAN COMPETITIVE ADVANTAGE PADA HOTEL BINTANG TIGA, EMPAT, DAN LIMA DI JAWA TIMUR - Fabiola Yoel; Saarce Elsye Hatane (Business Accounting Review, 2016)
This study aimed to examine the direct and significant influence of leadership style to learning organization, learning organization to financial performance, and leadership style to competitive advantage at the three-star hotel, four-star hotel, and five-star hotel in East Java. This study used quantitative approach and the data were obtained through the distribution of questionnaire to three-star hotel until five-star hotel in East Java. The data that were obtained, then processed by using PLS software. The result of this study showed that there was a positive and significant relationship of leadership style to learning organization, learning organization to competitive advantage, leadership style to competitive advantage at the three-star hotel until five-star hotel in East Java. Learning organization couldn’t become as intervening variable to leadership style and competitive advantage because of the direct relationship between leadership style and competitive advantage gave bigger influence than through learning organization.